Incorporating Equity, Diversity, Inclusion and Intersectionality in First-Year Engineering: An Exploration of Students’ Application to Teamwork - Janice Miller-Young; Danielle Gardiner Milln; Eklovepreet Singh (Teaching & Learning Inquiry: The ISSOTL Journal)
Teamwork skills are a vital learning outcome in higher education, yet negative interpersonal interactions within teams can diminish students’ sense of belonging and inclusion. To address this challenge, the introduction of equity, diversity, inclusion, and intersectionality (EDI&I) topics into course curriculums has been proposed. This study examines how integrating these concepts into a first-year engineering design course impacts students’ sense of inclusion and their ability to apply EDI&I principles to teamwork. Specifically, our research questions were: 1) To what extent did students experience a sense of belonging and uniqueness (inclusion) on their teams? 2) To what factors do students attribute their sense of belonging and uniqueness on their teams? And 3) How do students describe their design team experiences in relation to their ability to apply EDI&I? Data was collected through questionnaires from and interviews with forty-six participants using a qualitative empirical approach. Findings were that most students reported a strong sense of belonging and uniqueness within their teams, contributing to an overall feeling of inclusion. However, a small minority reported difficulties in applying EDI&I concepts to their teamwork. The discussion explores these difficulties and includes teaching strategies aimed at enhancing support for inclusive student teaming processes.